"Critical Agents of Change?": Opportunities and Limits to Children's Participation in Urban Planning. (May 2021) - Mansfield, Robyn G.; Batagol, Becky; Raven, Rob
Children's participation in urban planning impacts communities. A policy environment supports their participation, yet this is far from mainstream, particularly in areas of greatest vulnerability. This literature review demonstrates what we do and don't know about barriers and enablers to children's participation in urban planning. We identify key themes within participatory methods, processes, and structures that influence urban planning stages and methods and identify the consequences of children's inclusion or exclusion. We then argue for a research agenda that examines institutional impacts on urban planning and decisions that include or exclude children to contribute to a transformation of on-ground practices.